Solve for z y=-2z+9

Math
y=-2z+9
Rewrite the equation as -2z+9=y.
-2z+9=y
Subtract 9 from both sides of the equation.
-2z=y-9
Divide each term by -2 and simplify.
Tap for more steps…
Divide each term in -2z=y-9 by -2.
-2z-2=y-2+-9-2
Cancel the common factor of -2.
Tap for more steps…
Cancel the common factor.
-2z-2=y-2+-9-2
Divide z by 1.
z=y-2+-9-2
z=y-2+-9-2
Simplify each term.
Tap for more steps…
Move the negative in front of the fraction.
z=-y2+-9-2
Dividing two negative values results in a positive value.
z=-y2+92
z=-y2+92
z=-y2+92
Solve for z y=-2z+9

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top